Bullens circus. - Bullen Bros. ([Australia] : Bullen Bros Circus, 1930)
Poster promoting the circus. Features an illustration of various circus acts, with title only. Lettering probably opriginally reds, now orange.
Caption title.
Vivian James Carter Collection.
National Library of Australia's copy faded. Backed with tissue
Also available online
Alfred Percival Bullen (1896-1974) and his wife Lilian EtheI (1894-1965), began with a pony and a few pairs of roller-skates, travelling around country shows. By 1922 the Bullens organized their own circus. In the 1930s it travelled in Queensland with a show that included its own brass band and a menagerie. In the mid-1930s the show drifted to Western Australia and built one of Australia's most exciting circuses of the postwar era. By 1955 the two-ringed circus had twenty-six acts of international class, its own mobile power plant, three diesel lighting plants, a schoolteacher, fifty-six vehicles and caravans, and eighty permanent staff who called Bullen "Pop". Their white Rolls-Royce led the procession of long, brightly-decorated caravans from town to town.
Keywords: Bullen Bros. -- Posters; Circus -- Australia -- Posters; Circus animals -- Australia -- Posters; Circus posters -- Australia; Clowns -- Australia -- Posters; Advertising -- Circus -- Australia -- Posters; Amusements -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian